An Empirical Study of Activity, Popularity, Size, Testing, and Stability in Continuous Integration. - Gautam, Aakash; Vishwasrao, Saket; Servant-Cortés, Francisco Javier (My University, 2017)
A good understanding of the practices followed by software development projects can positively impact their success — particularly for attracting talent and on-boarding new members. In this paper, we perform a cluster analysis to classify software projects that follow continuous integration in terms of their activity, popularity, size, testing, and stability. Based on this analysis, we identify and discuss four different groups of repositories that have distinct characteristics that separates them from the other groups. With this new understanding, we encourage open source projects to acknowledge and advertise their preferences according to these defining characteristics, so that they can recruit developers who share similar values.
Keywords: Ingeniería del software; Continuous integration; Data science; Mining software repositories; Software testing